Anti-angiogenic potential of dog's tongue (pseudelephantopus spicatus (Juss.) Rohr.) plant extract in chick choroallantoic membrane - Don Karlo R. Nabus. 4 0 16; 5 (2017)
u
Thesis:(B.S. Biology) Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2